1981
DOI: 10.1088/0022-3727/14/3/017
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of low-frequency electrical noise in silicon resistors (in field effect devices)

Abstract: Excess and 1/f noise intensity has been measured between 80K and 380K in uniform cross-section silicon resistors with various geometries and surface conditions. It can be analysed as a fluctuating conductance proportional to (mobility)2, that is a carrier number fluctuation independent of temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

1983
1983
1996
1996

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
0
3
0
2
Order By: Relevance
“…Данная модель освещена и в книжной литературе (обзор современного состояния содержится в *; см. также 28 ). Как отмечено в 2 , она носит довольно спе-циальный характер и не может претендовать на общий охват фликкер-шума.…”
Section: • S (T')dunclassified
See 1 more Smart Citation
“…Данная модель освещена и в книжной литературе (обзор современного состояния содержится в *; см. также 28 ). Как отмечено в 2 , она носит довольно спе-циальный характер и не может претендовать на общий охват фликкер-шума.…”
Section: • S (T')dunclassified
“…Из резюме обзоров х > 2 видно, что вопросы о влиянии поверхности, соотношении «объемных» и «поверхностных» шумов и о выборе между мо-делями объемного шума пока далеки от ясности (особенно это относится к протяженным МОП-структурам 28 ). В 2 замечено, что модели флуктуа-ции числа носителей и флуктуации подвижности в определенной мере «перекрываются» друг с другом, так как, например, задержка носителей на ловушках должна приводить к флуктуациям их эффективной по-движности.…”
Section: • S (T')dunclassified
“…The spectral intensity, S, shows two types of spectra, the Lorentzian S -W O P + (f/f00)21 and a power law Sl/f' which is often referred to as l/fnoise since yis normally close to unity. In some systems l/f noise has been shown to be a resistance or emission fluctuation (Jones andFrancis 1975, Voss andClarke 1976) and this is widely accepted. Because of its general occurrence in most electrical systems a fundamental process is often sought, but none has been widely accepted.…”
Section: I/f Noisementioning
confidence: 99%
“…Hiatt etall981). Jones (1981) reportedexperiments on uniform channel devices which suggested that the noise was derived by a number fluctuation at the edge of the channel. The present work extends these measurements and analysis to allow for non-uniformities in the specimens.…”
Section: Excess Noise In Jfetmentioning
confidence: 99%
See 1 more Smart Citation